THE EFFECT OF COVID-19 ON STOCK MARKET RETURN IN CONSUMER GOODS SECTOR IN INDONESIA - Ong, Milenia; Marheni, Dewi Khornida (2021)
When 2019 is about to end, a new virus began to emerge called the coronavirus which is a very dangerous infectious virus because this virus can cause exposed humans to experience respiratory problems, lung infections, and can cause death. This coronavirus has caused many negative impacts on countries that have been exposed to this virus. Not only the health impact experienced by the exposed country but also from the aspect of the country's economy which has decreased drastically due to this virus. This study aims to see is there any effect of growth in confirmed cases, growth in deaths, trading volume, return (t-1), IHSG, and exchange rates on stock market returns in Indonesia consumer goods sector. The purposive sampling method was chosen by the researchers to take samples, namely secondary data with predetermined criteria based on the aims and objectives of the research, namely consumer good companies that have been registered on the IDX from 2 March 2020 until now. Researchers used Eviews 10 software to process data using the panel regression method with the selection of the best model, namely REM or Random Effect Model. The results concluded from the research analysis are that growth in confirmed cases and growth in deaths does not have significant impact on stock market returns in the consumer goods sector in Indonesia. Meanwhile, trading volume, return (t-1), IHSG, and exchange rate does have a positive significance on stock market returns in consumer goods sector in Indonesia. This research can help investors in making investment decisions, especially in Indonesia consumer goods sector.